Development and performance analysis of solar electric vehicle - Ahmed, Shoummo; Asrar, Sayeef; Nahif, Rizvan; Hossen, Md. Billal; Rubayet, Chowdhury Rabib (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.